Dietary Risk Assessment of Patulin in Cow Milk from Urmia of Iran - R. Tahmasebi; N. Vakili Saatloo; P. Sadighara; A. Abedini; M. Gheshlaghi; I. Limam; T. Zeinali (Journal of Food Quality and Hazards Control)
Background: Food contamination with mycotoxins is a global concern. Patulin, a mycotoxin secreted by molds, such as Penicillium expansum and Aspergillus clavatus, poses significant health risks. This study aimed to determine the presence of patulin in cow’s milk in Urmia, Iran, and to assess dietary intake of patulin and the associated Hazard Index. Methods: A total of 30 individual cow milk samples were collected during the summer of 2020 from a village near Urmia, Iran. Patulin levels were measured using High Performance Liquid Chromatography-Diode Array. Data was analyzed through SPSS. Results: Incidence rate of patulin in milk was 43.3%, with the mean of 0.34 µg/L. The Provisional Maximum Tolerable Daily Intake exceeded the estimated dietary intake, which ranged from 0.000063 for adults to 0.00086 µg/L for children. The Hazard Index was below one, indicating no non-carcinogenic health hazards. Conclusion: Patulin contamination was quantified in milk samples from Urmia, Iran. Given the potential health implications of patulin contamination, it is essential for government authorities and regulatory agencies involved in milk production to monitor mycotoxin residues and implement hazard control measures throughout the food supply chain.